Routledge Handbook of the Digital Environmental Humanities - Travis, Charles; Dixon, Deborah P.; Bergmann, Luke; Legg, Robert; Crampsie, Arlene (Routledge Environment and Sustainability Handbooks, 2023)
Cartography, Computing, Digital environmental humanities, Digital methods, Digital tools, Environment and sustainability, Environmental humanities, Environmental literature, Human geography, Indigenous, Informatics, Nature, Virtual spaces